2012
DOI: 10.1016/j.freeradbiomed.2012.08.576
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelation inhibits the development of pulmonary vascular remodeling

Abstract: Reactive oxygen species (ROS) have been implicated in the pathogenesis of pulmonary hypertension. Since iron is an important regulator of ROS biology, the present study examined the effect of iron chelation on the development of pulmonary vascular remodeling. The administration of an iron chelator, deferoxamine, to rats prevented chronic hypoxia-induced pulmonary hypertension and pulmonary vascular remodeling. Various iron chelators inhibited growth of cultured pulmonary artery smooth muscle cells. Protein car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…We previously reported that protein carbonylation mediates cell signaling in response to receptor activation by ligands such as endothelin-1 and PDGF [11-13,27]. However, IL-22 signaling may not utilize protein carbonylation for STAT3 activation, since the phosphorylation of STAT3 occurs 10 min after the IL-22 stimulation, while most proteins are not carbonylated until 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that protein carbonylation mediates cell signaling in response to receptor activation by ligands such as endothelin-1 and PDGF [11-13,27]. However, IL-22 signaling may not utilize protein carbonylation for STAT3 activation, since the phosphorylation of STAT3 occurs 10 min after the IL-22 stimulation, while most proteins are not carbonylated until 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Iron chelation has been shown to attenuate hypoxia-induced PH, pulmonary vascular remodeling and right ventricular hypertrophy in rats. In addition, carbonylation of proteins was increased in hypoxia-induced rats as well in the plasma of the patients with PAH indicative of oxidative stress[178]. Furthermore, PH in patients with idiopathic pulmonary fibrosis was shown to correlate with iron deposition in alveolar spaces[179].…”
Section: Iron Homeostasis and Pahmentioning
confidence: 99%
“…23,24 For example, in the monocrotaline model of PAH in SpragueDawley rats, dietary iron restriction has been shown to attenuate PA vascular remodeling and RV failure. 23 In that study by Naito et al, 23 an iron-deficient diet was initiated 1 day after monocrotaline injection and resulted in decreased PA wall thickness and a modest decrease in RV systolic pressures.…”
Section: Sutendra and Bonnet The Iron Paradigm Of Pah 1637mentioning
confidence: 99%